2019
DOI: 10.1111/1365-2435.13444
|View full text |Cite
|
Sign up to set email alerts
|

Are trade‐offs really the key drivers of ageing and life span?

Abstract: 1. Current thinking in life-history theory and the biology of ageing suggests that ageing rates, and consequently life spans, evolve largely as a function of trade-offs with reproduction. While various evolutionary constraints are generally acknowledged to exist, their potential role in determining ageing rates is rarely considered.2. This review integrates three types of information to assess the relative importance of constraints and trade-offs in shaping ageing rates: (a) empirical work on the presence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 118 publications
(117 reference statements)
1
79
0
4
Order By: Relevance
“…For example, early studies suggested that producing offspring is correlated with reduced lifespan among parents of both sexes (28,29), though in general the strongest evidence is for mothers. However, several studies have failed to demonstrate negative associations between reproduction and lifespan (123,124), and the evidence that greater reproductive effort promotes faster ageing through oxidative damage is inconsistent (26). We suggest that a wider range of metabolic traits relative to fitness merit consideration.…”
Section: Maintenance-reproduction (M-r)mentioning
confidence: 82%
See 2 more Smart Citations
“…For example, early studies suggested that producing offspring is correlated with reduced lifespan among parents of both sexes (28,29), though in general the strongest evidence is for mothers. However, several studies have failed to demonstrate negative associations between reproduction and lifespan (123,124), and the evidence that greater reproductive effort promotes faster ageing through oxidative damage is inconsistent (26). We suggest that a wider range of metabolic traits relative to fitness merit consideration.…”
Section: Maintenance-reproduction (M-r)mentioning
confidence: 82%
“…Moreover, other studies of the Tsimané found that despite their high fertility rates, markers of cardio-metabolic disease are amongst the lowest reported in human populations (127,128). The costs of reproduction may therefore be both "condition dependent, " i.e., varying in association with broader ecological conditions, and also outcome-dependent, i.e., varying across different markers of maintenance (26). In addition, they may also be shaped by experience in early life.…”
Section: Maintenance-reproduction (M-r)mentioning
confidence: 98%
See 1 more Smart Citation
“…Such positive co‐covariations can arise when the relative variation in resource acquisition exceeds the relative variation in resource allocation among individuals (van Noordwijk & de Jong, ). In addition, trade‐offs may only be evident under poor environmental conditions (Cohen et al, ). In large herbivores, poor environmental conditions can originate from multiple and often inter‐related factors such as high density, harsh weather, and low food availability.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies in the weakly dimorphic Alpine chamois (Rupicapra rupicapra) showed nonsignificant trends toward decreased longevity with increasing horn growth in males and females (Bleu, Loison, & Toïgo, 2014;Corlatti, Storch, Filli, & Anderwald, 2017). Such relationships may be stronger in populations experiencing poor environmental conditions, as reported for survival costs of reproduction (Cohen, Coste, Li, Bourg, & Pavard, 2019).…”
mentioning
confidence: 94%